The Existence of Mèkol Nyo’on Formula in Tradition of Inheritance Division in Madura - Maimun Maimun (Karsa: Journal of Social and Islamic Culture, 2016)
The tradition of the inheritance division in Madura knows a term namely mèkol nyo’on formula or formula 2:1. However, nowaday, the existence of that formula is very difficult to find in its implementation, although it still very sticks in each individual mind until now. This research describes what kind of traditions that have replaced the mekol nyo’on formula and why it happens in Madurese society whom are well known as very religious society. This research takes place in Pamekasan regency where most of the populations are moslem. By implementing sociological-descriptive approach, this research concludes that the tradition of mèkol-nyo’on formula has been replaced by the different formula, which emphasizes more on the goodness and benefits to all the heirs regardless of gender. with the main standard of equality in economic prosperity and humanity among fellow brothers in the family, where men and women have the same opportunity. Copyright (c) 2016 by KARSA. All right reserved DOI: 10.19105/karsa.v24i1.1009